EFFECT OF ECONOMIC GROWTH ON LEVEL POVERTY AND UNEMPLOYMENT RATE AS MEDIATION IN EAST NUSA TENGGARA PROVINCE - Fransiscus Nicodemus Naiola; Christian Timotius Peilouw; Donny Teguh Santoso Junias (Jurnal Ekonomi, 2023)
This research aims to determine the effect of economic growth on poverty levels with unemployment as mediation. This research uses a quantitative research method in associative form using one independent variable, namely economic growth, one dependent variable, namely the poverty level, and one moderating variable, namely the unemployment rate. According to Sugiyono (2016), the quantitative method is because research data is in the form of numbers and analysis uses statistics. The data used is a time series from 2018 to 2022 obtained from the Central Statistics Agency (BPS) of Nusa Tenggara Province. Economic growth influences poverty levels in NTT Province. This means that high or low economic growth has an impact on poverty rates. This is because the impact of economic growth is not felt by the poor in NTT Province. Unemployment moderates the influence of economic growth on poverty levels in NTT Province, which means that the number of unemployed continues to increase or decrease affecting economic growth and poverty.